Conducting polymer coated optical microfiber sensor for alcohol detection - Yeong, S.C.; Kok, S.L.; Sulaiman, W.H.; Seng, N.G.; Sook, W.P. (Elsevier, 2014)
In this study, an optical microfiber sensor coated with conducting polymer, polyaniline (PAni) is investigated as a detector for alcohols. PAni was synthesized by chemical oxidation method and dioctyl sodium sulfosuccinate (AOT) was used as the dopant. PAni was then coated onto the microfiber by drop coating method. The proposed sensor exhibits wavelength shift in the output spectrum in response to various types of alcohols at different concentrations. The output response can be associated with the solution refractive index and number of alkyl substituent of alcohol. Furthermore, this sensor also shows excellent repeatability in the detection. In conclusion, a conducting polymer based microfiber optical sensor for alcohol detection with simple, low cost and effective set-up was successfully achieved in this study.